2018
DOI: 10.1371/journal.pmed.1002672
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and reasons for women’s, family members’, and health professionals’ preferences for cesarean section in China: A mixed-methods systematic review

Abstract: BackgroundChina has witnessed a rapid increase of cesarean section (CS) rates in recent years. Several non-clinical factors have been cited as contributing to this trend including maternal request and perceived convenience. We aimed to assess preferences for mode of delivery and reasons for preferences for CS in China to inform the development of future interventions to mitigate unnecessary CSs, which are those performed in the absence of medical indications.Methods and findingsWe conducted a mixed-methods sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
116
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 63 publications
(146 reference statements)
13
116
0
1
Order By: Relevance
“…23,24 We evaluated the risk of bias by assessing the eligibility criteria, sample size, representativeness (whether a sampling methodology was used appropriately to produce an estimate representative of the target population or if a convenience sample or special group was selected), response rate, data collection tool, clarity of the questions/statements and definition of the outcome, clarity of the objective, ethical considerations, and consistency between research question and data reported (Appendix S2). 25 We present the evaluation results for each question for each included study. The potential risk of bias was characterised as follows: eligibility criteria (low risk, defined eligibility; high risk, not defined); sample size (low risk, 100 subjects or more; high risk, <100 or not explained); data collection tool (low risk, described with references; moderate risk, described without references; high risk, not described); definition of the outcome (low risk, well defined; high risk, improperly defined); clarity of results data (low risk, reported with numerators and denominators; high risk, not clearly reported), and representativeness (low risk, representative; moderate risk, not described or somehow representative; high risk, selected group).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…23,24 We evaluated the risk of bias by assessing the eligibility criteria, sample size, representativeness (whether a sampling methodology was used appropriately to produce an estimate representative of the target population or if a convenience sample or special group was selected), response rate, data collection tool, clarity of the questions/statements and definition of the outcome, clarity of the objective, ethical considerations, and consistency between research question and data reported (Appendix S2). 25 We present the evaluation results for each question for each included study. The potential risk of bias was characterised as follows: eligibility criteria (low risk, defined eligibility; high risk, not defined); sample size (low risk, 100 subjects or more; high risk, <100 or not explained); data collection tool (low risk, described with references; moderate risk, described without references; high risk, not described); definition of the outcome (low risk, well defined; high risk, improperly defined); clarity of results data (low risk, reported with numerators and denominators; high risk, not clearly reported), and representativeness (low risk, representative; moderate risk, not described or somehow representative; high risk, selected group).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…However, 40% expected to have a C-section when arriving at the hospital to give birth (76). Women that expect or prefer a C-section justify it by expressing their fear of fetal distress and mortality, excessive pain, or fear of trauma to the vagina (14)(15)(16)76).…”
Section: Creating Tailored Health Education Interventionsmentioning
confidence: 99%
“…Countries with alarming cesarean rates, such as Brazil, Dominican Republic, Egypt, Taiwan, China, India, and Iran, have many similar non-clinical factors identified as contributors to the high rates, as well as unique factors to each country's context (14)(15)(16)(17)(18)(19). Researchers found that social and cultural beliefs of women, families, and communities in these countries result in a similar viewpoint that a cesarean is a safer delivery mode for the mother and child when compared to vaginal birth.…”
mentioning
confidence: 99%
“…The CS rate in China began to rise in the early 1980s, with a sharp rise in the mid-1990s, and continued to rise from 28.8% in 2008 to 34.9% in 2014 [2,3]. Reasons for the rapid rise in CS rate in China were multifactorial [4][5][6]. Among the commonly cited reasons are fear of labor pain, concerns about complications such as urinary incontinence and lower quality of sex life after vaginal delivery, misconception of CS being safer than vaginal delivery for the baby, poor experience of previous vaginal delivery, and auspicious dates [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for the rapid rise in CS rate in China were multifactorial [4][5][6]. Among the commonly cited reasons are fear of labor pain, concerns about complications such as urinary incontinence and lower quality of sex life after vaginal delivery, misconception of CS being safer than vaginal delivery for the baby, poor experience of previous vaginal delivery, and auspicious dates [3,4]. The shortage of nurses/midwives and the large volume of deliveries often lead to more convenient and scheduled CS.…”
Section: Introductionmentioning
confidence: 99%